Tursun Fakih Gazavatnamesinin Ağızbilimsel Özellikleri - Develi, Hayati (Gökkubbe, 2004)
In the former article, we have stated three dialect groups of the Old Anatolian Turkish according to the phonological criteria. The first group had sub-group which can be identified the feature of b- > p- & c- > ç- assourdissement and k > g sonorisation. This sub-group can be seen in Mukaddima fi'ilm al-ibadât by Kutb addîn İznikî (XVth century). In this article we deseribed the dialectological features of the This text of the XVth century also belongs to the same sub-group.
Dialectological Features in Gazavat-Name of Tursun Fakih
Keywords: Historical Linguistics; Old Anatolian Turkish; Dialectology of Turkish; Gazavatname of Tursun Fakih